Advances in cotton science : botany, production, and crop improvement /: botany, production, and crop improvement. (2019) - Maiti, R. K, 1938-; Aruna Kumari, C. H, 1972-; Huda, Abul Kalam Samsul; Mandal, Debashis; Begum, Sameena
No abstract available